Data Policies and Data Archives: A New Paradigm for Academic Publishing in Economic Sciences? - Sven Vlaeminck; Lisa-Kristin Herrmann (New Avenues for Electronic Publishing in the Age of Infinite Collections and Citizen Science. Proceedings of the 19th International Conference on Electronic Publishing, 2015)
In our paper we summarise the findings of an empirical study in which a sample of 346 journals in economics and business studies were examined. We regard both the extent and the quality of journals' data policies, which should facilitate replications of published empirical research. The paper presents some characteristics of journals equipped with data policies and gives some recommendations for suitable data policies in economics and business sciences journals. In addition, we also evaluate the journals' data archives to roughly estimate whether these journals really enforce data availability. Our key finding is that we are currently not able to determine a new publishing paradigm for journals in economic sciences.
Keywords: A1; B4; M1; C8; 330; reproducibility; replication; economics; business studies; academic publishing; data policies; data archives; social sciences